Devin Rhodes is dead - Kam, Jennifer Wolf (Mackinac Island Press, 2014)
To most people Cassandra and Devin are teenage girls who are best friends--but Cassandra actually resents the arrogant and bossy Devin, and when Devin turns up dead in a ravine Cassandra is wracked by her guilty secret.